Fabrication of chitosan and poly (vinyl alcohol) blend membranes with different concentration of chitosan - Nurain, Mansor (2008)
Nowadays, the technology of membrane has become famous and widely used in the world. Many types of membrane have been invented including the chitosan (CS) membrane and also the poly (vinyl alcohol) (PVA) membrane. The objectives of this research are to fabricate the blend membrane using of chitosan and PVA with different concentration of chitosan, to study the performances and the morphology changes of each membrane. In this study, chitosan was blended with PVA to get the flat sheet blend membranes. PVA was used as the polymer matrix and CS as the functional polymer to provide amine group for the flat sheet blend membrane in order to make it adsorptive. There are two types of CS/PVA blend membrane which are Blend I (2.5wt% of CS) and Blend II (3.0wt% of CS). Acetic acid was used as a solvent for CS and PVA in preparing the dope solution. Formaldehyde and H2SO4 was used to form crosslinking between PVA and chitosan. NaOH solution was used as both the external and internal coagulants. These membranes were being tested on pure water permeability (PWP), rejection (R), flux rate (J) and also the morphologies changes in each membrane. The adsorption performance of the flat sheet blend membrane was evaluated through the adsorption of BSA solution and lysozime. The results reveal that, PWP was increased by increasing of concentration of CS. Besides, the pores size was increase when the concentration of CS was increased. The rejection and also the flux rate also increase by increasing the concentration of CS. In a nut shell, different concentration of CS enhanced the performances and the morphologies of the membrane.